The diagnosis of leptospirosis complicated by pulmonary tuberculosis complemented by metagenomic next-generation sequencing: A case report - Shi, Jichan; Wu, Wenjie; Wu, Kang; Ni, Chaorong; He, Guiqing; Zheng, Shilin; Cheng, Fang; Yi, Yaxing; Ren, Ruotong; Jiang, Xiangao (Frontiers in Cellular and Infection Microbiology, 2022)
Leptospirosis is a zoonotic infection caused by the pathogenic Leptospira. Leptospirosis is transmitted mainly through contact with contaminated rivers, lakes or animals carrying Leptospira. Human leptospirosis has a wide range of non-specific clinical manifestations ranging from fever, hypotension and myalgia to multi-organ dysfunction, which severely hampers the timely clinical diagnosis and treatment of leptospirosis. Therefore, there is an urgent clinical need for an efficient strategy/method that can be used for the accurate diagnosis of leptospirosis, especially in critically ill patients. Here we report a case of a 75-year-old male patient with clinical presentation of fever, cough and diarrhea. Initial laboratory tests and a computed tomography (CT) scan of the chest suggested only tuberculosis. The patient was finally diagnosed with pulmonary tuberculosis (PTB) combined with leptospirosis by sputum Xpert MTB RIF, epidemiological investigations and delayed serological testing. Further, through metagenomic next-generation sequencing (mNGS) of clinical samples of cerebrospinal fluid (CSF), urine, plasma and sputum, the causative pathogens were identified as Mycobacterium tuberculosis complex and Leptospira spp. With specific treatment for both leptospirosis and tuberculosis, and associated supportive cares (e.g. haemodialysis), the patient showed a good prognosis. This case report suggests that mNGS can generate a useful complement to conventional pathogenic diagnostic methods through more detailed etiological screening (i.e. at the level of species or species complex).